Occurrence of foodborne pathogens in Italian soft artisanal cheeses displaying different intra- and inter-batch variability of physicochemical and microbiological parameters - Pasquali, Frédérique; Valero, Antonio; Possas, Arícia; Lucchi, Alex; Crippa, Cecilia; Gambi, Lucia; Manfreda, Gerardo; De Cesare, Alessandra (Frontiers in Microbiology, 2022)
Artisanal cheeses are produced in small-scale production plants, where the lack of a full automation and control of environmental and processing parameters suggests a potential risk of microbial contamination. The aim of the present study was to perform a longitudinal survey in an Italian artisanal factory producing a spreadable soft cheese with no rind to evaluate the inter and intra- batch variability of physico-chemical and microbial parameters on a total of 720 environmental and cheese samples. Cheese samples were additionally collected during 15 days of storage at constant temperatures of 2 ºC and 8 ºC, as well as a dynamic profile of 2 °C for 5 days and 8 °C for 10 days. Furthermore, Enterobacteriaceae isolates were identified at species level to have a better knowledge of the environmental and cheese microbiota potentially gathering human pathogens. High inter-batch variability was observed for lactic acid bacteria (LAB) and total bacteria count (TBC) in cheese at the end of production but not for pH and water activity. Temperature of 8 °C was associated to a significantly higher load of Enterobacteriaceae in cheeses belonging to batch 6 at the end of storage as well as the temperature corresponding to the highest increase in LAB and TBC loads over cheese shelf-life. Results from Generalized Linear Mixed Models indicated that the water drainage in the warm room and in the packaging area were associated with higher levels of TBC and Enterobacteriaceae in cheese. Regarding foodborne pathogens, no sample was positive for verotoxigenic Escherichia coli (VTEC) or Listeria monocytogenes, whereas six Staphylococcus aureus and one Salmonella Pullorum isolates were collected in cheese samples during storage and processing respectively. Regarding Enterobacteriaceae, 166 isolates were identified at species level from all batches, with most isolates belonging to Klebsiella oxytoca and pneumoniae, Enterobacter cloacae, Hafnia halvei and Citrobacter freundii evidencing the need to focus on standardization of microbial quality of cow milk as well as on hygienic procedures of cleaning and disinfection especially in warm and maturation rooms. Further studies should be performed to investigate the potential pathogenicity and antimicrobial resistance of the identified Enterobacteriaceae species in artisanal cheeses.